A possible association between early life factors and burden of functional bowel symptoms in adulthood - Johanna Wennerberg; Shantanu Sharma; Peter M. Nilsson; Bodil Ohlsson (Taylor & Francis Group, 2021)
Objective The studies of early life factors and development of functional bowel diseases show inconsistent results. We therefore examined associations between certain early life factors and functional bowel symptoms in adulthood. Design Population-based cross-sectional study. Setting Weight and height were measured and questionnaires were completed at the time point of enrollment in MOS. Subjects 1013 participants in the Malmö Offspring Study (MOS) without organic bowel disease with data available from the Swedish Medical Birth Registry. Main outcome measures Associations were calculated between gestational age, birth weight, small-for-gestational-age and Apgar score from the Birth Registry, and symptoms according to the visual analog scale for irritable bowel syndrome (VAS-IBS) (abdominal pain, diarrhea, constipation, bloating and flatulence, vomiting and nausea, and symptoms' influence on daily life) or self-reported IBS using logistic regression. Results In all, 253 (25.0%) participants reported bowel symptoms during the past 2 weeks and 179 (17.7%) self-reported IBS; conditions which were strongly associated (p < 0.001). Female sex and chronic stress were two independent factors more common among participants with bowel symptoms compared with asymptomatic participants (p < 0.001). Early life factors were not associated with presence of overall bowel symptoms (p = 0.080), any specific bowel symptoms or self-reported IBS. Lower birth weight (p = 0.038) and being born small for gestational age (p = 0.043) were associated with severe influence of intestinal symptoms on daily life in adulthood. Conclusions Lower birth weight and small for gestational age are not associated with the presence of overall bowel symptoms but with more pronounced influence of such symptoms on daily adult life.Key points Lower gestational age tended to be associated with functional bowel symptoms in adulthood. Lower birth weight and being small for gestational age are associated with increased negative influences of symptoms on daily life in adulthood. Patients born preterm or with low birth weights may be at increased risk to develop functional bowel symptoms later in life.